The power threshold concept in ski specific strength training - Schiefermüller, C.; Müller, E.; Feldbacher, P. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
To cope with the complex demands of alpine skiing the athletes need highly developed motoric abilities. Based on global motoric abilities elite alpine ski racers have to work on the ski specific fitness training. Their main interest should be based on technique specific strength, endurance and coordination training (Müller, 2002). The skier should have reached a highly developed standard in his specific physical fitness, in order to being able to tolerate the volume and intensity of the first training session on snow (glacier) in the early summer time, since progressive fatigue during one week ski training can have negative effects on the quality of the training. Therefore the level of physical fitness highly influences a successful and continued improvement in competitive techniques. To guarantee a fast and complete recovery after each run and each day of snow training we assume that the level of aerobic capacity is of high importance (Vogt, 2005; Hartmann, 2005). Elite alpine skiers spend a high amount of time in endurance training. High velocities in addition to small turn radii lead to high forces (more than three times body weight) in all disciplines of alpine skiing. When steering the ski along its side cut the forces occur already at the beginning of the turn. In spite of the short phase of the edge switching the skier has to handle the forces during the whole turn without any chance to recover. Highly developed skiing techniques include high forces on the inner leg. In addition to this small knee angles (about 70 degrees) due to inward leaning lead to high demands on the skiers… leg muscles. To resist centrifugal and gravity forces the skier hast to improve his strength abilities. With a high level of maximum strength the skier can overcome the external forces even at the end of the run without loosing any quality due to fatigue in his steering abilities. This resistance against fatigue when dealing with high and repeated forces is highly determined by the level of strength endurance.Strength endurance is defined as the resistance against the loss of power during repeated exercise. (Harre, 1986; Nicolaus, 1995a; Martin, 1993). In addition to the training of maximum strength (hypertrophy and intramuscular coordination) the skier also has to concentrate on the development of his strength endurance. Based on a global, unspecific strength endurance training, sport specific exercises should be of high importance in the skiers` fitness program. Appropriate training devices help to realise specific exercises. (Raschner, 1997; Schiefermüller, 2005). One important criteria of specific training is to ensure the quality and quantity of the movement until the end of the exercise. The precision of the movement has to be guaranteed for each repetition. A decrease in the amount and in the velocity of motion due to fatigue should not occur (for example: less knee extension).